Role of systemic high‐dose methotrexate and combined approaches in the management of vitreoretinal lymphoma: A single center experience 1990‐2018. Issue 3 (5th December 2018) - Castellino, Alessia; Pulido, Jose S.; Johnston, Patrick B.; Ristow, Kay M.; Nora Bennani, N.; Inwards, David J.; Macon, William R.; Micallef, Ivana N. M.; King, Rebecca L.; Salomao, Diva R.; Witzig, Thomas E.; Habermann, Thomas M.; et al.
Abstract: Vitreoretinal lymphoma (VRL) management remains a challenge. We present 72 patients with VRL, diagnosed at Mayo Clinic between 1990‐2018. Three nondiffuse large B‐cell lymphoma (DLBCL) histology cases were excluded. Among 69 DLBCL, 33 patients had primary VRL (PVRL), 18 concurrent intraocular and central nervous system (CNS) or systemic disease and 18 secondary VRL. Patients received intraocular chemotherapy (intraocular injections of rituximab or metothrexate or steroids or in combination), radiotherapy, systemic or combined systemic plus intraocular treatment in 9, 10, 35, and 15 cases, respectively. Among primary and concurrent VRL, median failure free survival (FFS), CNS relapse‐free survival (CNS‐RFS) and overall survival (OS) were: 1.8, 4.9, and 4.1 years, respectively; among PVRL, median FFS, CNS‐RFS, and OS were: 2.6 year, Not Reached and 9.3 year, respectively. No CNS relapse occurred beyond 4 years in PVRL. Median OS for patients diagnosed between 1990 and 1999 vs between 2000 and 2018 was 1.5 vs 9.4 years, respectively ( P = .0002). OS was significantly higher in PVRL, as compared with concurrent VRL ( P = .04). Previous immunosuppression and poor performance status were predictive of worse outcome. In PVRL, a combined systemic and intraocular therapy showed higher FFS ( P = .002) and CNS‐RFS ( P = .003), but no differences in OS. Among 18 secondary VRL, at a median follow‐up of 1.1 year after vitreoretinal relapse, median FFS and OS were 0.3 and 1.3 years. An improvement in survival of VRL has been observed over the decades. PVRL should undergo combined systemic and intraocular chemotherapy to prevent CNS progression.